Pengaruh Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) dengan Metode Eksperimen Terhadap Keterampilan Proses Sains dan Hasil Belajar Fisika pada Siswa SMA Negeri 1 Labuapi Tahun Pelajaran 2015/2016 - Juraini Juraini; Muhammad Taufik; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2016)
This study is aimed to know the influence of cooperative learning type STAD by experiment method towards science process skill and studentÃ¢â¬â¢s output in learning physics at SMAN 1 Labuapi in academic year 2015/2016. The method used in this study was quasi experimental design of untreated control group design pretest-posttest. The population of this study was the overall students of X class at SMAN 1 Labuapi, where there are 4 classes with random sampling technique in taking the subject. Two sample was taken as the subject of this study where X-D as experimental class which was treated using cooperative learning of type STAD by experiment method and X-A as control class. Technique of data analysis of this study was two sample t-test. Based on the result of this study, it can be concluded: (1) there was the influence of cooperative learning of type STAD by experiment method towards science process skill of studentÃ¢â¬â¢s physics, (2) there was the influence of cooperative learning of type STAD by experiment method towards studentÃ¢â¬â¢s output in learning physics.